THE EFFECTS OF ACADEMIC SUPERVISION BY PRINCIPAL AND WORK MOTIVATION ON TEACHERS’ PROFESSIONALISM - Hasan, Aiza Nirmala; Hariri, Hasan; Rini, Riswanti; Handoko, Handoko (Abjadia : International Journal of Education, 2024)
This study examines the influence of academic supervision by the school principal and work motivation on teachers' professionalism. Employing a quantitative approach with an ex post facto design, the research encompasses all junior high school teachers in South Lampung Regency. A sample of 130 teachers was obtained through simple random sampling. Data collection involved distributing questionnaires, and the analysis used simple linear regression. The findings reveal that both academic supervision by the school principal and work motivation have a positive and significant impact on teachers' professionalism. Specifically, in State Junior High Islamic Schools in South Lampung Regency, increased academic supervision by the head of the madrasah correlates with higher levels of teachers' professionalism. Similarly, increased work motivation corresponds with enhanced teacher professionalism. Therefore, the study recommends that school principals enhance the quality of academic supervision and foster greater work motivation among teachers to achieve higher professionalism.